Myelodysplastic Syndrome-Associated SRSF2 Mutations Cause Splicing Changes by Altering Binding Motif Sequences - Masaki, So; Ikeda, Shun; Hata, Asuka; Shiozawa, Yusuke; Kon, Ayana; Ogawa, Seishi; Suzuki, Kenji; Hakuno, Fumihiko; Takahashi, Shin-Ichiro; Kataoka, Naoyuki (Frontiers in Genetics, 2019)
Serine/arginine-rich splicing factor 2 (SRSF2) is a member of the SR protein family that is involved in both constitutive and alternative mRNA splicing. Mutations in SRSF2 gene were frequently reported in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). It is imperative how these mutations affect SRSF2-mediated splicing and cause MDS. In this study, we tried to characterize SRSF2 mutants (P95H, P95L and P95R), which were detected in MDS patients. We first determined subcellular localization of those mutants and wild type protein in HeLa cells. We found that all of them showed nuclear localization. In vitro splicing reaction also revealed that mutant proteins could support splicing reaction and associate with pre-mRNA and mRNA. These results suggested that mutants could affect splicing patterns in the cell nuclei. We then have established K562, human myeloid leukemia cells, expressing myc-tagged either wild type or mutant SRSF2 proteins. Total RNAs were recovered from those cells to analyze RNA splicing patterns. RNA sequence analyses revealed that both wild type and mutants affected splicing of approximately 3,000 genes. Although splice site sequences adjacent to the affected exons showed no significant difference compared to the total exons, exonic motif analyses with both inclusion- and exclusion-enhanced exons demonstrated that wild type and mutants have different binding sequences in exons. These results strongly suggest that mutations of SRSF2 in MDS change binding properties of SRSF2 to exonic motifs and this affects in some exon inclusion/exclusion resulting in aberrant splicing.